Effects of Dietary Tribulus terrestris Extract Supplementation on Growth, Feed Utilization, Hematological, Immunological, and Biochemical Variables of Nile Tilapia Oreochromis niloticus - Gültepe, Nejdet; Acar, Ümit; Kesbiç, Osman Sabri; Yılmaz, Sevdan; Yıldırım, Önder; Türker, Ali (SAABRON PRESS, 2014)
The present study was conducted for 88 days to evaluate the effect of dietary Tribulus terrestris supplementation on growth performance, feed utilization, and hematological, immunological, and biochemical indices of Nile tilapia, Oreochromis niloticus. A total of 144 Nile tilapia, average body weight 2.61±0.35 g, were divided into four experimental treatments. There were three replicates of each treatment. Four isonitrogenous (40% CP) and isolipidic (10% CL) experimental diets contained T. terrestris extract at levels of 0, 200, 400 and 600 mg/kg respectively. Growth performance and feed utilization of Nile tilapia were significantly higher (p<0.05) in all treatment groups fed with T.terrestris extract supplemented diets than those fed the control diet. There were no significant differences between body composition of fish (p>0.05). Hematocrit, hemoglobin, mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and myeloperoxidase variables were not significantly affected by herb extract (p>0.05). However, mean corpuscular volume (MCV) value and lysozyme activity increased with increasing T. terrestris extract (p<0.05). Serum albumin, total protein, and triglyceride levels were not affected by T. terrestris extract. Serum globulin and glucose levels increased and cholesterol levels decreased in Nile tilapia fed with herbal supplemented diets. The results of the present study suggest that Nile tilapia fed diets containing at least 400 mg/kg T. terrestris extract enhanced growth performance, feed utilization, hematological, immunological, and biochemical indices.
Keywords: herb extract; hematology; Tribulus terrestris; Fish culture--Israel; Fish culture; immunostimulant; Nile tilapia; 2. Zero hunger; 6. Clean water; 3. Good health; 13. Climate action